Transcriptomic and metabolomic analyses for providing insights into the influence of polylysine synthetase on the metabolism of Streptomyces albulus - Congcong Lian; Min Zhang; Jiaqi Mao; Yuanyu Liu; Xiuwen Wang; Linghui Kong; Qingshou Yao; Jiayang Qin (figshare, 2022)
Abstract ε-poly-l-lysine (ε-PL) is the main secondary metabolite of Streptomyces albulus, and it is widely used in the food industry. Polylysine synthetase (Pls) is the last enzyme in the ε-PL biosynthetic pathway. Our previous study revealed that Pls overexpressed in S. albulus CICC11022 result in the efficient production of ε-PL. In this study, a Pls gene knockout strain was initially constructed. Then, genomic, transcriptomic and metabolomic approaches were integrated to study the effects of the high expression and knockout of Pls on the gene expression and metabolite synthesis of S. albulus. The high expression of Pls resulted in 598 significantly differentially expressed genes (DEGs) and 425 known differential metabolites, whereas the inactivation of Pls resulted in 868 significant DEGs and 374 known differential metabolites. The expressions of 8 and 35 genes were negatively and positively associated with the Pls expression, respectively. Subsequently, the influence mechanism of the high expression and inactivation of Pls on the ε-PL biosynthetic pathway was elucidated. Twelve metabolites with 30% decreased yield in the high-expression strain of Pls but 30% increased production in the Pls knockout strain were identified. These results demonstrate the influence of Pls on the metabolism of S. albulus. The present work can provide the theoretical basis for improving the production capacity of ε-PL by means of metabolic engineering or developing bioactive substances derived from S. albulus.
Keywords: Genetics